2022
DOI: 10.1007/s10238-022-00972-4
|View full text |Cite
|
Sign up to set email alerts
|

External radiotherapy combined with sorafenib has better efficacy in unresectable hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Advanced hepatocellular carcinoma (HCC) has a very low resectable rate. This meta-analysis aimed to compare efficacy of three combination strategies in treatment of advanced unresectable HCC with a view of guiding future selection of the best combination therapy for sorafenib and local therapy. A search was conducted to identify relevant literature published between April 2013 and May 2022, and then compared efficacy of sorafenib combined with external radiotherapy (SOF + RT), sorafenib with transarterial chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Some studies have shown that the combination of TACE, external radiotherapy, internal radiotherapy and sorafenib or lenvatinib has an positive clinical effect. 4,21,[24][25][26] Su and others demonstrated that radiotherapy combined with PD-1 and targeted therapy has survival benefits, 27 further proving the bright prospect of TACE combined with target immunotherapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies have shown that the combination of TACE, external radiotherapy, internal radiotherapy and sorafenib or lenvatinib has an positive clinical effect. 4,21,[24][25][26] Su and others demonstrated that radiotherapy combined with PD-1 and targeted therapy has survival benefits, 27 further proving the bright prospect of TACE combined with target immunotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…TACE can upregulate tumor antigens and "danger" signals, which can make the tumor more responsive to immunotherapy. 20,21 At present, the development of TACE has shown an increasing trend. Studies have shown that stable homogeneous iodide preparation technology (SHIFT) can fully disperse ICG (indocyanine green) into lipid iodine for transcatheter embolization combined with fluorescence guided resection.…”
Section: Discussionmentioning
confidence: 99%
“…This proposed BBB model could act as a future backbone for evaluating the efficacy of treatments for glioma and the passage of drug cargos through the BBB for testing cutting-edge glioma theranostics. Treatment of gliomas has long been a major challenge of neuro-oncology due to the tumor heterogeneity and the diffuse and infiltrative nature of the growth of the high-grade gliomas and hence much attempt has been devoted to improving the efficacy of glioma treatment comprising using external beam radiation or external beam radiation and soferanib ( 52 , 53 ). This proposed BBB model could aid in improving translational research on the impact of external beam radiation or other chemotherapies for glioma treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In China, HCC is the second leading cause of cancer-related deaths ( 4 ). The development of HCC is a multistage and multifactorial process, and HCC is heterogeneous and characterized by high tumor invasiveness, frequent recurrence, and poor prognosis ( 5 ). Some serum biomarkers were used in the early diagnosis and prognosis of HCC ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%